Effects of an Antimutagenic 1, 4‐Dihydropyridine AV‐153 on Expression of Nitric Oxide Synthases and DNA Repair‐related Enzymes and Genes in Kidneys of Rats with a Streptozotocin Model of Diabetes Mellitus. Issue 5 (30th May 2016) - Ošiņa, Kristīne; Rostoka, Evita; Isajevs, Sergejs; Sokolovska, Jelizaveta; Sjakste, Tatjana; Sjakste, Nikolajs
Abstract: Development of complications of diabetes mellitus (DM), including diabetic nephropathy, is a complex multi‐stage process, dependent on many factors including the modification of nitric oxide (NO) production and an impaired DNA repair. The goal of this work was to study in vivo effects of 1, 4‐dihydropyridine AV‐153, known as antimutagen and DNA binder, on the expression of several genes and proteins involved in NO metabolism and DNA repair in the kidneys of rats with a streptozotocin (STZ)‐induced model of DM. Transcription intensity was monitored by means of real‐time RT‐PCR and the expression of proteins by immunohistochemistry. Development of DM significantly induced PARP1 protein expression, while AV‐153 (0.5 mg/kg) administration decreased it. AV‐153 increased the expression of Parp1 gene in the kidneys of both intact and diabetic animals. Expression of H2afx mRNA and γH2AX histone protein, a marker of DNA breakage, was not changed in diabetic animals, but AV‐153 up‐regulated the expression of the gene without any impact on the protein expression. Development of DM was followed by a significant increase in iNOS enzyme expression, while AV‐153 down‐regulated the enzyme expression up to normal levels. iNos gene expression was also found to be increased in diabetic animals, but unlike the protein, the expression of mRNA was found to be enhanced by AV‐153 administration. Expression of both eNOS protein and eNos gene in the kidneys was down‐regulated, and the administration of AV‐153 normalized the expression level. The effects of the compound in the kidneys of diabetic animals appear to be beneficial, as a trend for the normalization of expression of NO synthases is observed.